Implementación del sistema de puesta a tierra de los equipos en la base de la torre 2 de la radio universitaria 98.5 MHz. - Guarnizo Jiménez, Jonathan Fernando (2015)
Grounding, is a set of electrodes that provide a conductive electrical contact between the middle in which they are immersed in installation, equipment, metallic structures, etc., which have a big importance for the protection and good performance of electrical and electronic equipment having a principal function the security of staff working whit this, avoiding that a fault current or atmospheric discharger can damage it. The present study focuses in the investigation about grounding through national standards such as IEEE 80-200, NORMA ECUATORIANA DE LA CONSTRUCCIÓN (NEC), NTC 2050, where specify the correct installation, use and maintenance to show the current state about grounding. Another factors that affect soil resistivity as temperature, salinity, seasonal variations, etc., the method that was used to measure soil resistivity was Frank Wenner or four points, and was detailed another methods to find the resistivity as fall of potential, method of triangulation, etc. Then proceeded to install a system about grounding in the base of college radio tower whit triangular mesh with three electrodes of copper of 1.80 meters.